Assessment of ecological flow in river basins at a global scale: Insights on baseflow dynamics and hydrological health - Hao Chen; Saihua Huang; He Qiu; Yue-Ping Xu; Ramesh S.V. Teegavarapu; Yuxue Guo; Hui Nie; Huawei Xie; Jingkai Xie; Yiting Shao; Yuping Han (Ecological Indicators, 2025)
Understanding global baseflow dynamics is essential for sustainable water management and ecosystem resilience. This study introduces a comprehensive four-stage framework for quantifying novel spatiotemporal patterns in global baseflow variability and their critical implications for hydrological and ecological health. Key innovations include: (1) An ensemble machine learning approach demonstrating superior accuracy in runoff gap-filling compared to single-model methods; (2) Identification of distinct global decline patterns, revealing that 45.73 % of basins exhibit significant decreasing trends (p < 0.05), concentrated disproportionately in arid and warm temperate zones, suggesting heightened vulnerability linked to hydroclimate drivers; (3) Analysis establishing that baseflow provides a disproportionately vital contribution (>70 % in many basins) to dry-season streamflow globally, acting as a crucial ecological buffer; and (4) An integrated BFI-Tennant assessment revealing pronounced regional disparities in ecological flow health, with consistently good conditions in North America, South America, and Europe contrasting sharply with prevalent deficits in parts of Africa, Australia, and the Middle East, strongly correlating with water stress and climate regimes. Critically, our findings reveal emergent principles: the framework demonstrates that baseflow decline is not uniform but exhibits regionally accelerated vulnerability, and that its dry-season dominance underpins the stability of river ecosystems where it persists. This study presents a robust and transferable methodology, delivering new global insights essential for prioritizing conservation and management strategies in increasingly water-stressed basins.